Answers

2014-08-02T23:03:49+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Square root of [ (x^2+8x+15) (x^2+x-6) (x^2+3x-10) ]
we can get an idea that in such cases that, the polynomials (quadratic expressions) given above may be factorized ..
x²+8x+15  = (x+a)(x+b) => a+b = 8    a*b = 15  easy to find a = 5  b = 3  as factors of 15 are easy
x²+x-6  = (x+c)(x+d)    => c+d = 1  c*d = -6  factors of -6 are 3 & 2  since sum is +1,  c=+3  d= - 2
x² + 3x - 10 = (x+e)(x+f)  =>  e+f = 3  ef = -10  factors of 10 5, 2. since sum is 3, e= +5,  f= -2

NOW squaretoot  is equal to
square root [   (x+3) (x+5)  (x+3)  (x-2)  (x+5) (x-2)  ]
square root [  (x+3)² (x+5)²  (x-2)² ]
=  (x+3) (x+5) (x-2)

=========================================================
If factorizaion is difficult, then do as :
(x^2+8x+15) = 0      Δ = 8² - 4*15 = 4    => x = (-8 +- 2 ) /2 = -5 or -3
     so  (x^2+8x+15) = (x - -5)  (x - -3)  = (x+5)(x+3)
(x^2+x-6) =0          Δ = 1 +24 = 25    => x = -1 +- 5  / 2  = -3 or 2
     so factors  (x - -3)(x - 2)
similarly the other expression
0